La bancassurance : phénomène universel - Moreau, Rémi (Assurances, 1992)
The phenomenon of "Bancassurance", meaning the merging of the banking and insurance industries, has become more widespread since the emergence of the single European market. The author briefly discusses the new relationships between financial institutions in Canada, the United States, Western Europe and Asia. As we approach the 21st century, ties between banks and insurers have never been as close. Some experts predict that the globalization of insurance may ultimately and irreversibly bring down financial barriers. On the other hand, others do not hesitate to criticize the new phenomenon and claim that combining the risk of each financial institution into a single conglomerate risk will increase the public's risk and dangerously disperse the capital base that sustains it. The debate has yet to be settled.